2016
DOI: 10.3174/ajnr.a4882
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Features of Malignant Lacrimal Sac and Nasolacrimal Duct Tumors

Abstract: The purpose of this study was to present the imaging features of primary and secondary malignant lacrimal sac and nasolacrimal duct tumors and their pattern of tumor spread in 18 patients. The most common tumor histology in our series was squamous cell carcinoma. In 15/18 patients, tumor involved both the lacrimal sac and duct at the time of diagnosis. In 11/16 patients on CT, the nasolacrimal bony canal was smoothly expanded without erosive changes. The medial canthus region (16/18) was a frequent site of dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…The clinical signs and symptoms of lacrimal sac tumors are nonspecific [ 7 ], but include medial canthal swelling [ 4 ], epiphora [ 3 ]. Therefore, some may be initially misdiagnosed or the diagnosis may be delayed [ 7 - 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical signs and symptoms of lacrimal sac tumors are nonspecific [ 7 ], but include medial canthal swelling [ 4 ], epiphora [ 3 ]. Therefore, some may be initially misdiagnosed or the diagnosis may be delayed [ 7 - 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Imaging such as CT scan or magnetic resonance imaging (MRI) can help guide the diagnosis, staging, and treatment plans [ 13 ]. CT scan is preferred over MRI for viewing the extent of the tumor and bone metastasis [ 3 ]. A CT scan should be done if the patient presents with the following findings: a hard consistency mass at the lacrimal sac, palpable mass over the medial canthal ligament, or orbital deformities due to the effect of the mass [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Imaging features of a malignancy in the nasolacrimal sac include a contrast-enhancing mass with expansion or erosion of nasolacrimal bone, and possible extension to the orbit, nasal cavity, and sinuses. [11][12][13] In a series of malignant lacrimal sac and nasolacrimal duct tumors, Kumar et al 13 reported that smooth expansion of the bony canal was more common than bony erosion, and that contrast enhancement was demonstrated in most cases on both computed tomography and magnetic resonance imaging. However, for locally advanced malignant lacrimal sac and duct tumors, it is difficult to distinguish primary tumors from secondary tumors by imaging alone.…”
Section: Discussionmentioning
confidence: 99%
“…However, for locally advanced malignant lacrimal sac and duct tumors, it is difficult to distinguish primary tumors from secondary tumors by imaging alone. 13 The diagnosis of nasolacrimal duct metastasis must be confirmed by histology.…”
Section: Discussionmentioning
confidence: 99%
“…Axial and coronal CT scans could determine the extent of lesions, relationship with surrounding tissues, and bone destruction. The malignancy originating from dacryocyst may grow into the nasolacrimal duct, leading to nasolacrimal duct expansion [14,15]. If imaging examination shows nasolacrimal duct expansion, especially accompanied by bone destruction; a great deal of attention should be paid to the possibility of malignancy from dacryocyst.…”
Section: Discussionmentioning
confidence: 99%